Gender-Sensitive Communication Strategies in Reducing Bias and Stereotyping in the Media - Sari Rossa Agustina (International Journal Labs, 2026)
In Indonesia, online gender-based violence (KBGO) surged by 348% between 2019 and 2020 (Komnas Perempuan, 2021), reflecting the pervasive influence of patriarchal culture in digital media spaces. Despite growing awareness, mass media and social media continue to exploit women as objects rather than subjects, reinforcing gender stereotypes through discriminatory content and language. This research aims to explain the strategies for creating gender-sensitive communication in the media, with a particular focus on social media platforms, within the Indonesian context. Employing a qualitative approach through a narrative literature review, this study systematically synthesized academic sources obtained from Google Scholar, DOAJ, and Garuda Kemdikbud databases (publication years 2011–2024) using thematic analysis. The findings reveal that gender-sensitive social media communication can be achieved through four key strategies: 1) strengthening digital literacy for the public by building networked digital communities to promote gender empowerment through education and online discussion spaces; 2) educating media users about women’s rights and needs across political, social, cultural, and safety dimensions using gender-friendly language; 3) presenting gender-neutral content by depicting individuals as active subjects rather than passive objects; and 4) engaging men as allies to dismantle patriarchal culture through equitable communication practices. These findings contribute to the development of gender-sensitive media frameworks applicable to digital communication policies and practices in Indonesia.